Ketentuan Hukum Shalat Jumat dalam Risalah Cahaya Suluh: Perspektif Ulama Kontemporer dan Pembelajaran PAI di Sekolah Umum dan Madrasah - Nijo Nijo; Erwin Mahrus (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Friday prayers have kaifiyah regarding the terms and pillars where scholars have similar opinions, there are also those who differ in certain matters. The discussion of this paper discusses the Friday prayer in the Treatise of Light Suluh which is conferred by his contemporaries with Islamic Religious Education Lessons in Madrasas. Motede discusses studies in the analysis of journals and books that make related to Friday prayers. After the process of discussion and study, the first conclusion was obtained, that the Treatise of Light Suluh Maharaja Imam Basiuni Imran was written to provide solutions to the problem of dissent and the practice of Friday prayers and dhuhur prayers on Friday in Sambas and its surroundings. Second, Maharaja Imam Basiuni Imran in deciding the law of worship is always based on the arguments and opinions of scholars in the matter of Friday prayers Basiuni Imran is very moderate and flexible even though he is a Shafi'i school because Sambas conditions require a fatwa on the validity of Friday prayers carried out by less than 40 people including no longer performing dhuhur prayers on Friday if they have performed Friday prayers. Third, Islamic religious education learning in schools that discuss Friday prayers for the MTs / Junior High School level is quite adequate, but for high school / vocational / MA it is necessary to deepen the material